A finite-difference time-domain method for solving electromagnetic problems with bandpass-limited sources - Pursel, J.D.; Goggans, P.M. (IEEE transactions on antennas and propagation, 1999)
The complex-envelope representation of bandpass-limited signals is used to formulate a bandpass-limited vector wave equation and a new finite-difference time-domain (FDTD) scheme that solves the bandpass-limited vector wave equation is presented. For narrow-band electromagnetic systems, this new method allows the time step to be several orders of magnitude larger than current FDTD formulations while maintaining an amplification factor equal to one. Example results obtained by this method are presented and compared with analytic solutions.